Systematic review and network meta-analysis of the effects of plant active substance on quality of life in breast cancer patients - Wang, Lu; Xu, Xiaofan; Guo, Mengmeng; Dong, Yanxu; Ding, Helin; Hao, Shuai; Huo, Liqun; Song, Yuqing; Gu, Jun; Yu, Zhenghong (Frontiers in Pharmacology, 2025)
BackgroundPlant-derived active substances are increasingly recognized as potential adjuvant therapies in breast cancer treatment, with emerging evidence suggesting their positive impact on both treatment outcomes and quality of life (QoL). This study aims to evaluate the effects of fifteen active substances—soy capsules, Helixor A, Viscum album [L.] extracts, Withania somnifera, Paullinia cupana, P. ovata husk, ginseng, curcumin, Jollab, ginger, fermented soybean extract, mistletoe extract, robuvit®, peppermint extract, and Chlorella extract—on QoL in patients with breast cancer (BC).MethodsA comprehensive literature search was performed across PubMed, EMBASE, Cochrane Library, and Web of Science up to January 2025. The primary outcomes of interest included QoL, fatigue, pain, physical functioning, nausea, and role and emotional functioning. Statistical analyses were carried out using StataMP 15.1 software. Treatment efficacy was assessed using Surface Under the Cumulative Ranking Curve (SUCRA) probabilities. Additionally, cluster analysis was conducted to examine the multidimensional effects of natural extracts across these seven clinical outcomes.ResultsAfter screening, 18 eligible studies were included, encompassing 2062 patients and evaluating 15 substances. The analysis incorporated patient-reported outcomes from multiple trials: QoL (11 studies), fatigue (10 studies), pain (8 studies), physical functioning (8 studies), nausea (7 studies), role functioning (7 studies), and emotional functioning (7 studies). Based on SUCRA values, Withania somnifera was identified as the most effective treatment for enhancing QoL (99.4%) (SMD = 4.66, 95% CI: 3.47–5.85), physical functioning (100.0%) (SMD = 7.78, 95% CI: 6.61–8.96), role functioning (100.0%) (SMD = 8.10, 95% CI: 6.89–9.32), and emotional functioning (100.0%) (SMD = 5.71, 95% CI: 4.81 to 6.61) were more effective than the standard treatment. Moreover, Withania somnifera was found to be the most promising option for reducing fatigue (99.9%), pain (100.0%), and nausea (98.6%).ConclusionThe network meta-analysis indicates that Withania somnifera was effective in enhancing quality of life and contributed to a reduction in therapeutic side effects in BC patients. Our findings support the therapeutic potential of plant bioactive substances in breast cancer care; however, further clinical validation of their efficacy is warranted.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251006422.